Clinical Prediction Model for Obstructive Sleep Apnea among Adult Patients with Habitual Snoring. (July 2019) - Lin, Hsin-Ching; Lai, Chi-Chih; Lin, Pei-Wen; Friedman, Michael; Salapatas, Anna M.; Chang, Hsueh-Wen; Lin, Meng-Chih; Chin, Chien-Hung
Objective: To identify standard clinical parameters that may predict the presence and severity of obstructive sleep apnea/hypopnea syndrome (OSA). Design: Case series with chart review. Setting: Tertiary academic medical center. Subjects and Methods: A total of 325 adult patients (274 men and 51 women; mean age, 44.2 years) with habitual snoring completed comprehensive polysomnography and anthropometric measurements, including modified Mallampati grade (also known as updated Friedman's tongue position [uFTP]), tonsil size grading, uvular length, neck circumference, waist circumference, hip circumference, and body mass index (BMI). Results: When the aforementioned physical parameters were correlated singly with the apnea/hypopnea index (AHI), we found that sex, uFTP, tonsil size grading, neck circumference, waist circumference, hip circumference, thyroid-mental distance, and BMI grade were reliable predictors of OSA. When all important factors were considered in a multiple stepwise regression analysis, an estimated AHI can be formulated by factoring sex, uFTP, tonsil size grading, and BMI grade as follows: –43.0 + 14.1 × sex + 12.8 × uFTP + 5.0 × tonsil size + 8.9 × BMI grade. Severity of OSA can be predicted with a receiver operating characteristic curve. Predictors of OSA can be further obtained by the "OSA score." Conclusion: This study has distinguished the correlations between sex, uFTP, tonsil size, and BMI grade and the presence and severity of OSA. An OSA score might be beneficial in identifying patients who should have a full sleep evaluation.